The transition to adulthood of young adults with IDD: Parents' joint projects. (23rd August 2017) - Young, Richard A.; Marshall, Sheila K.; Stainton, Tim; Wall, Jessie M.; Curle, Deirdre; Zhu, Ma; Munro, David; Murray, John; El Bouhali, Asmae; Parada, Filomena; Zaidman‐Zait, Anat
Abstract : INTRODUCTION: Parents have found the transition to adulthood for their sons or daughters with intellectual and/or developmental disabilities (IDD) particularly challenging. The literature has not examined how parents work together and with others in face of this transition nor has it highlighted parental goals in this process. This study used a perspective based on joint, goal‐direct action to describe the projects that Canadian parents engaged in together and with others relative to this transition. Methods: Using the qualitative action‐project method, joint projects between parents and with others were identified from their conversations and followed for 6 months. Findings: Three groups of projects were described: equipping the young adult for adult life, connecting for personal support and managing day‐to‐day while planning for the future. Conclusions: Parents act together and with others relative to the transition to adulthood of their young adult children with IDD. These projects are complex and differ in goals, steps, resources and emotional regulation and motivation.